Generation Z and the Job-Hopping Phenomenon: An Exploration of Career Preferences and Expectations - Dwiyono, Luhur Haris; Hartono, Arif (International Journal of Economics, Business and Innovation Research, 2026)
This study examines how Generation Z workers in Yogyakarta interpret work and engage in job hopping within their early career experiences. Using a qualitative phenomenological approach, in-depth interviews were conducted with six Generation Z individuals who had experienced multiple job transitions. The findings indicate that Generation Z holds a hybrid orientation toward work, integrating economic survival, career development, and value actualisation simultaneously. Job hopping is perceived not as impulsive or disloyal behaviour, but as a rational and adaptive career strategy when employment fails to meet financial, developmental, or psychosocial expectations. Career decisions are shaped by accumulated work experiences, educational background, family responsibilities, and local labour-market conditions, particularly relatively low wage levels. Participants demonstrate high emotional awareness and agency in responding to expectation reality misalignment through adaptive coping strategies, including skill development, parallel job searching, and planned exits.